2019
DOI: 10.1155/2019/5085373
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Composition of Genomic TMPRSS2-ERG Rearrangements in Prostate Cancer

Abstract: There is increasing interest in the use of cell-free circulating tumor DNA (ctDNA) as a serum marker for therapy assessment in prostate cancer patients. Prostate cancer is characterized by relatively low numbers of mutations, and, in contrast to many other common epithelial cancers, commercially available single nucleotide mutation assays for quantification of ctDNA are insufficient for therapy assessment in this disease. However, prostate cancer shares some similarity with translocation-affected mesenchymal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…DSRCT breakpoints were further notable for the complete absence of filler bases at their breakpoint junction. Filler bases have been identified in approximately 15–20% of breakpoints in other fusion-based tumors and are a byproduct of NHEJ [ 33 , 35 ]. Together, these findings suggest DSRCT genomic breakpoints may form predominantly through MMEJ rather than NHEJ [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…DSRCT breakpoints were further notable for the complete absence of filler bases at their breakpoint junction. Filler bases have been identified in approximately 15–20% of breakpoints in other fusion-based tumors and are a byproduct of NHEJ [ 33 , 35 ]. Together, these findings suggest DSRCT genomic breakpoints may form predominantly through MMEJ rather than NHEJ [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of cell-free circulating tumour nucleotides in blood samples is another promising new molecular strategy for non-invasive tumour monitoring in prostate cancer [ 79 ]. CfDNA may be more suitable than CTCs to estimate therapy efficiency in patients with early-stage disease [ 80 ].…”
Section: Blood-based Liquid Biopsy Marker Candidatesmentioning
confidence: 99%
“…50% of patients results from the fusion of the androgen-regulated gene, transmembrane protease serine 2 gene ( TMPRSS2 , chr21q22.2), with E-twenty-six (ETS)-related gene ( ERG , chr21q22.3). This rearrangement is detectable in CTCs or as cfDNA and might be considered as a highly tumour-specific, non-invasive molecular biomarker for therapy assessment, risk stratification and relapse detection [ 79 , 87 , 88 ]. Furthermore, prostate cancer carrying this rearrangement can regulate the recruitment and infiltration of regulatory T cells (Tregs) in the tumour [ 89 ].…”
Section: Blood-based Liquid Biopsy Marker Candidatesmentioning
confidence: 99%
“…The proteolytic cleavage and activation of hemagglutinin protein are also essential for the viral infectivity of influenza A virus (strains of H1N1, H3N2, and H7N9) [73,74]. Recent studies revealed that a gene fusion of TMPRSS2 to erythroblast transformation-specific (ETS) transcription factors is commonly observed in prostate cancer tissues [75,76]. Among these, fusion of TMPRSS2 and ERG is the most common (approximately 50%) chromosomal rearrangement [75,76].…”
Section: Tmprss2 In Pcmentioning
confidence: 99%
“…Recent studies revealed that a gene fusion of TMPRSS2 to erythroblast transformation-specific (ETS) transcription factors is commonly observed in prostate cancer tissues [75,76]. Among these, fusion of TMPRSS2 and ERG is the most common (approximately 50%) chromosomal rearrangement [75,76]. However, no apparent proteolytic activity in this fusion protein has been reported (the protein mainly acts as a transcription factor).…”
Section: Tmprss2 In Pcmentioning
confidence: 99%